Gagasan Menyatukan Umat Islam Indonesia Melalui Kalender Islam - Susiknan Azhari (AHKAM : Jurnal Ilmu Syariah, 2015)
This article discussed many kinds of Islamic calendar in Indonesia, including Muhammadiyah, PBNU, Indonesia Taqwim Standard, and Islam PERSIS calendar. The results found each calendar has a different system in the initial launch of lunar month. Data reckoning found for 19 years (2015-2033) that it is differences possibilities for eight times. To resolve this discrepancy, the authors offered mutakamil Hilaltheory as a middle way between wujudul hilal and visibility, so the distinction has to be completed and the Eid can be universally implemented.DOI: 10.15408/ajis.v15i2.2869